RESEARCH ON THE MAINTAINABILITY EVALUATION METHOD OF SHIP POWER CABINS IN NARROW SPACES - Song, Tingxin; Li, Mingyin (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
In order to solve the design problems of narrow-space maintainability of ship power cabins at the research and development (R&D) stage, ergonomics simulation and systems engineering evaluation techniques are used to study narrow-space maintainability by taking a ship power cabin as an object. Firstly, the core indexes of comfort, maintenance workspace, accessibility and visibility are identified, and weights are determined after consulting technical experts; then, maintenance tasks are decomposed into basic operation units to guide visualization simulation; finally, operation units are analyzed one by one to identify maintenance weaknesses and make recommendations for improvement. Taking "pipeline oil leakage maintenance" as an example, the feasibility of the method is verified by comparing and analyzing the maintainability before and after improvement. The results show that this method can identify and solve design problems of maintainability in narrow spaces of ship power cabins at the R&D stage and has practical engineering value.